TECHNOLOGY PARK IN THE MODEL OF REGIONAL INNOVATIVE ECONOMY - Nikolay D. Tskhadaya; Vasily A. Zykov; Oksana I. Belyaeva (Высшее образование в России)
Abstract: The article presents a triadic model of the formation and development of regional innovation economy, featuring a high level of macroeconomic integration. The authors analyze the role of technology park as one of the basic elements of this model; and justify the effectiveness of the relationship between the technical University and the regional technology park on the example of Ukhta State Technical University.